2011
DOI: 10.3109/14767058.2010.531327
|View full text |Cite
|
Sign up to set email alerts
|

Why women request cesarean section without medical indication?

Abstract: Although majority of the women had wrong idea or no idea about the risks and benefits of CD, nearly half of them indicated that women can always demand CDMR. This study shows that basal knowledge of the women should be improved by education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 20 publications
2
54
1
3
Order By: Relevance
“…33 This indicates a lack of information available to pregnant women, because a number of studies have shown that infants born by caesarean section are exposed to more risks compared with those born vaginally. A recent review summarises short-term as well as longer-term effects of delivery by prelabour caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…33 This indicates a lack of information available to pregnant women, because a number of studies have shown that infants born by caesarean section are exposed to more risks compared with those born vaginally. A recent review summarises short-term as well as longer-term effects of delivery by prelabour caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Furthermore, another study reported that almost half of women thought a cesarean delivery without medical indication should be performed upon request, despite minimal knowledge about the risks and benefits of one. 58 We advocate policies and strategies that support informed and shared decision-making for women, their families, and clinicians. Nevertheless, there are instances where the spontaneous onset of labor occurs before 39 weeks or planned birth is unavoidable, and it is important that appropriate interventions and support in early childhood are developed and provided for these potentially vulnerable children.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that an increased preference for cesarean delivery was associated with an increased level of education, perhaps due to increased knowledge about the risks and benefits of each mode of delivery. However, previous results showing a relationship between level of education and choice of cesarean delivery in the absence of any medical indication found that most of these women did not have detailed knowledge about the benefits and risks of these modes of delivery [13].…”
Section: Discussionmentioning
confidence: 77%